The Level Of Knowledge on the Use Of NSAIDs As Analgesic For Dysmenorrhea Case In Faculty of Health Universitas Muhammadiyah Lamongan - Primanitha Ria Utami; Devi Ristian Octavia; Selly Septi Fandinata (Universitas Islam Lamongan, 2020)
Non-steroidal anti-inflammatory (anti-inflammatory) drugs, or better known as NSAIDs (Non-Steroidal Anti-Inflammatory Drugs) or NSAIDs are a group that has analgesic (pain reliever), anti-pyretic (fever) properties. to determine the level of knowledge on the use of NSAIDs as anti-pain in cases of dysmenorrhea in the University of Muhammadiyah Lamongan. The research design used in this research is descriptive, in taking the sample using the total sampling technique. Collecting data by distributing questionnaires with data analysis presented in tabular form. The results of this study indicate that of the 266 respondents, almost all respondents know about knowledge of dysmenorrhea well (83.8%). In the results of this study, there were still respondents who did not know the proper use of NSAIDs as analgesic. So in this case the role of pharmaceutical personnel is needed in providing information or education to people who consume NSAIDs, in order to achieve a quality of life for the community and avoid unwanted therapeutic responses. Keywords : NSAID ; dysmenorrhea ; analgesic